Fertility preferences and unmet need for family planning in women with multiple sclerosis - López-Reyes, Lorena; Guío-Sánchez, Claudia; González-Uribe, Catalina; Cárdenas-Robledo, Simón (Frontiers in Neurology, 2022)
Background Most women with Multiple Sclerosis (MS) have childbearing potential. Although fertility and pregnancy are not affected by MS, the fertility preferences of women with MS can change due to the risk of complications for the mother and/or adverse pregnancy outcomes resulting from the disease or its treatment. Objectives To describe fertility preferences (FP) and their associated factors, to estimate the Unmet Need for Family Planning (UNFP), use of contraceptives, and history of exposure to disease-modifying therapies (DMTs) during pregnancy in women with MS. Methods In a cross-sectional observational study, a random sample of women with MS were surveyed with the FP subset of the Demographic and Health Survey of Colombia. Factors associated with FP were evaluated through bivariate and logistic regression analysis. The proportion of pregnancies exposed to DMTs, UNFP, and use of contraceptives was estimated. Results Of the 141 women interviewed, 101 women had childbearing potential, of which 49 did not want to have children, 38 were sterilized, 33 wanted to have more children, 19 were undecided, and 2 stated they were unable to bear children (menopause or hysterectomy). No MS related variables were associated with the preference to have more children. Age (OR: 0.91; 95% CI 0.84 – 0.98) and the number of children (OR: 0.23; 95% CI 0.09 – 0.58) decreased the likelihood of desire for children. Of 116 sexually active women, 87.06 % (101) were using contraceptives, and among them, four were using fertility-awareness methods and withdrawal. The UNFP was estimated at 6.03% and was not significantly different from the general population. 82 pregnancies were identified, of which 48 occurred after diagnosis, and 25 were exposed to DMTs. Conclusion FP in women with MS is not associated with clinical variables. A large proportion of women choose not to have children and prefer to use permanent contraceptive methods. Although the frequency of contraceptive use was high, some women have UNFP and use low efficacy contraceptive methods, which may result in unplanned pregnancies.